2021
DOI: 10.1149/1945-7111/abd5fc
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Volume Changes and Associated Stresses in Ge Electrodes Due to Na/Na+ Redox Reactions

Abstract: In situ electrochemical cells were assembled with an amorphous germanium (a-Ge) film as working electrode and sodium foil as reference and counter electrode. The stresses generated in a-Ge electrodes due to electrochemical reaction with sodium were measured in real-time during the galvanostatic cycling. A specially designed patterned a-Ge electrode was cycled against sodium and the corresponding volume changes were measured using an AFM; it was observed that sodiation/desodiation of a-Ge results in more than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Subhajit et al reported that the amorphous Ge thin film undergoes ∼240% volume change after the full sodiation, which corresponds to roughly Na 1.4 Ge. 56 Also, the amorphous Ge nanowires are observed to suffer from a ∼300% volume expansion upon sodiation, in which the reaction terminates at Na 1.6 Ge. 34 Hence, it is anticipated that the formation of the Na 3 Ge phase would induce a larger volume expansion (more Na is stored), thereby possibly more susceptible to mechanical failures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subhajit et al reported that the amorphous Ge thin film undergoes ∼240% volume change after the full sodiation, which corresponds to roughly Na 1.4 Ge. 56 Also, the amorphous Ge nanowires are observed to suffer from a ∼300% volume expansion upon sodiation, in which the reaction terminates at Na 1.6 Ge. 34 Hence, it is anticipated that the formation of the Na 3 Ge phase would induce a larger volume expansion (more Na is stored), thereby possibly more susceptible to mechanical failures.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitatively, compressive stress of 0.56 GPa is observed when a Ge film is sodiated at room temperature, above which a higher compression is expected. 56 On the other hand, the electrical resistivities of Ge and its sodiated phases should also play a role. Although no direct evidence can be found on how Na inclusion affects the electrical conductivity of the sodiated Ge, the sodiated Sn (the element below Ge in the periodic table) is reported to be more electrically resistive as the Na content increases, not uncommon for intermetallic phases.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the focus was clearly based on lithium‐ion batteries and only limited data exists on post‐lithium systems. [ 111,112 ] Thoroughly investigated lithium‐based anode materials include lithium titanate (LTO), [ 106 ] silicon, [ 113 ] germanium, [ 114 ] and aluminum. [ 115 ] Research on cathodes includes layered oxides for lithium‐ion batteries [ 116 ] and the olivine FePO 4 .…”
Section: Methodsmentioning
confidence: 99%